Liquid/Solid Interfaces: Studies of Kinetics of Isotope Exchange - M. Kosmulski; M. Jaroniec; J. Szczypa (Adsorption Science & Technology, 1985)
Many radiotracer methods based on the phenomenon of isotope exchange are used in the studies of interfaces. These methods enable an investigation of heterogeneous systems at equilibrium. Studies of the kinetics of isotope exchange also give valuable information about systems in which ions appearing in the solution are at the equilibrium state with the same ions adsorbed on the solid particles or built into their crystalline lattice. Such systems, in which the solids are either ionic crystals or ion-exchanger beads, are taken into account in the present paper. In spite of wide applications, the phenomenon of heterogeneous isotope exchange is rather poorly understood and the fragmentary results reported in the literature do not lead to unambigous conclusions concerning the mechanism of this phenomenon. In the present review, the theoretical models of isotope exchange are discussed and compared with experimental results. The results are also discussed with respect to enlargement of applications of isotope exchange to investigation of heterogeneous systems, e.g. containing porous solid particles.